Characterization of N6-methyladenosine in cattle-yak testis tissue - Wang, Xingdong; Pei, Jie; Guo, Shaoke; Cao, Mengli; Kang, Yandong; Xiong, Lin; La, Yongfu; Bao, Pengjia; Liang, Chunnian; Yan, Ping; Guo, Xian (Frontiers in Veterinary Science, 2022)
N6-methyladenosine (m6A) is the most common form of eukaryotic mRNA modification, and it has been shown to exhibit broad regulatory activity in yeast, plants, and mammals. The specific role of m6A methylation as a regulator of spermatogenesis, however, has yet to be established. In this experiment, through a series of preliminary studies and methylated RNA immunoprecipitation sequencing, the m6A map of cattle-yak testicular tissue was established as a means of exploring how m6A modification affects cattle-yak male infertility. Cattle-yak testis tissues used in this study were found to contain sertoli cells and spermatogonia. Relative to sexually mature yak samples, those isolated from cattle-yak testis exhibited slightly reduced levels of overall methylation, although these levels were significantly higher than those in samples from pre-sexually mature yaks. Annotation analyses revealed that differentially methylated peaks were most concentrated in exonic regions, with progressively lower levels of concentration in the 3’-untranslated region (UTR) and 5’-UTR regions. To further explore the role of such m6A modification, enrichment analyses were performed on differentially methylated and differentially expressed genes in these samples. For the cattle-yaks vs. 18-month-old yaks group comparisons, differentially methylated genes were found to be associated with spermatogenesis-related GO terms related to the cytoskeleton and actin-binding, as well as with KEGG terms related to the regulation of the actin cytoskeleton and the MAPK signaling pathway. Similarly, enrichment analyses performed for the cattle-yaks vs. 5-year-old yaks comparison revealed differentially methylated genes to be associated with GO terms related to protein ubiquitination, ubiquitin ligase complexes, ubiquitin-dependent protein catabolism, and endocytotic activity, as well as with KEGG terms related to apoptosis and the Fanconi anemia pathway. Overall, enrichment analyses for the cattle-yaks vs. 18-month-old yaks comparison were primarily associated with spermatogenesis, whereas those for the cattle-yaks vs. 5-year-old yaks comparison were primarily associated with apoptosis.